Attitudes of EFL University Teachers in Public Universities in Khartoum State ,towards Research Publication ,a Case Study - Albashier, Batool Ibrahim; Abdelkareem, Ahazeej Abdellateef (Gezira Journal of Educational Sciences and Humanities; مجلد 19 عدد 1 (2022), 2023)
Abstrac t This study investigates the attitudes of EFL university teachers in Khartoum State towards publishing scientific research and the challenges that they encounter to publish their research. The study used the descriptive approach. A questionnaire was used as a tool for data collection. The data was analyzed with the Statistical Packages of Social Sciences SPSS. The sample of the study included forty EFL university teachers from eight public universities of Khartoum State. The results showed that most university teachers face difficulties finding suitable journal with high rank to publish in. In addition to the lack of funds for their studies. The study recommended giving more facilitation to encourage teachers to conduct research.